DESAIN TEMPAT KERJA BERBASIS ENGINEERING CONTROL SEBAGAI PENGENDALIAN COVID-19 - Ajeng Fitria Utami (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The current COVID-19 pandemic has had a negative impact on the world of work, one of which is the informal industry. To protect informal workers from exposure to COVID-19, control efforts can be carried out through the UKK Post from the Puskesmas, one of which is by developing an engineering control-based workplace design that is in accordance with ISO/PAS 45005:2020. Design of this research is Research and Development Level 1, using instruments in the form of questionnaires, interview guidelines, and validation sheets. The sample in this study was the Head of the UKK Post and the UKK Pos UKK cadre at Puskesmas X with the sampling technique being purposive sampling, and 3 validators. The results of the research conducted indicate that the development of workplace designs carried out is the development of ventilation, room layout, floor signs or markers, and physical barriers in the administrative, production and finishing areas. Workplace design development products that have been made get grades in a decent category with minor improvements based on the validation carried out with the validators.